Prevalence of Pre-Diabetes and unreported diabetes mellitus in population aged 45 years and above in owerri municipality, Imo State Nigeria - I S I Ogbu; E C Azodo; A U Chinwuba (International Journal of Medicine and Health Development, 2012)
Background: Unreported diabetes mellitus and glucose intolerance have substantial clinical importance. Glucose intolerance precedes diabetes mellitus and it is associated with cardiovascular complications. Subjects with prediabetes have near normal glycated haemoglobin and may only be detected when oral glucose tolerance was performed. Early detection may prevent or delay diabetes and its complications. This study determined the prevalence of un-reported diabetes mellitus and glucose intolerance in Owerri Municipality, Imo State of Nigeria. Methodology: 1,012 apparently healthy subjects aged 45 years and above were recruited for the study. Their anthropometric parameters were measured using standard methods and plasma glucose was measured using glucose oxidase method. Diagnosis of diabetes and pre-diabetes was made according to WHO criteria. Results: A total of 157 subjects had pre-diabetes giving a prevalence of15.5%. Subjects of aged 40 – 59 years were mostly affected. IFG alone, IGT alone and a combination of IFG +IGT occurred in 30.6%, 62.4% and 7.0% respectively of the study population. The highest prevalence of IFG was recorded in the 40 – 49 years age group while that of IGT occurred in the 50 – 59 years range. A combination of IFG and IGT occurred rarely in the study population, 7.0% and none was detected after the age of 59 years. A greater proportion of males, 18%, than females, 14.5%, had pre-diabetes. Unreported diabetes was detected in 8.6% of the study population, most of them in the 50 – 69 years age bracket. It was more prevalent in the female subjects, 11.1% than in the male subjects 4.4%. The mean BMI, WHR, FPG and 2hppG of the pre-diabetes subjects were 28.76 ±3.5kg/m2, 0.94 ±0.14, 5.28 ± 0.75 mmol/l and 8.43 ± 1.57mmol/l respectively. Among the male pre-diabetes subjects, peak values for BMI and FPG occurred after 70 years of age while in their female counterparts, peak mean values for these parameters occurred much earlier, 40 -59 years range. Conclusions: The report showed high prevalence of glucose intolerance and un-reported diabetes mellitus in the population. The need for regular screening of the population for glucose intolerance was highlighted in order to reduce the incidence of diabetes and its complications.